Mediated Corporeality in the Philosophical Perspectives of Ihde and Foucault - Ayala Aragón, Oscar Ronulfo (2026)
This article focuses on understanding how technologies influence bodily experience, understood as corporeality, and the formation of subjectivity; exploring the perspectives of Ihde and Foucault. For this purpose, focal points of analysis are addressed: the notion of the body and its relationship with corporeality, corporeality and situationality, the link between embodiment and technological alienation, interaction and embodiment in the context of embodiment, the connection between embodiment and subjectivity, and technological mediation in bodily experience related to power. Differences and similarities between both philosophical approaches are highlighted.